PENGARUH SOCIAL MEDIA MARKETING, E-WOM DAN KUALITAS PELAYANAN TERHADAP MINAT BELI PADA PERUSAHAAN JASA PERCETAKAN PT. TEMPRINA MEDIA GRAFIKA - IA Cynthia Saisaria Mandasari; Sagung Putu Intan Sri Laksmi; I Gusti Ayu Agung Istri Sari Dewi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
This study aims to analyze the effect of Green Product, Green Innovation, and Green Brand This study aims to analyze the influence of Social Media Marketing, Electronic Word of Mouth (E-WOM), and Service Quality on consumers’ Purchase Intention at the printing service company PT Temprina Media Grafika Denpasar. The background of this research is based on the increasingly intense competition in the printing service industry and the growing role of digital media in influencing consumer behavior, which requires companies to effectively utilize social media, build positive E-WOM, and improve service quality in order to attract consumer purchase intention. The research method used is a quantitative approach with data collection techniques through the distribution of questionnaires to 90 respondents who are customers of PT Temprina Media Grafika Denpasar. The data analysis techniques include validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that partially Social Media Marketing, E-WOM, and Service Quality have a positive and significant effect on consumers’ Purchase Intention. Simultaneously, these three independent variables also have a significant effect on consumers’ Purchase Intention. The conclusion of this study is that Social Media Marketing, E-WOM, and Service Quality, both partially and simultaneously, have a significant influence on consumers’ Purchase Intention at PT Temprina Media Grafika Denpasar. Based on these results, it is recommended that the company further optimize social media marketing strategies, encourage the creation of positive E-WOM, and continuously improve service quality to sustainably increase consumers’ purchase intention.